2021
DOI: 10.3390/ijerph181910309
|View full text |Cite
|
Sign up to set email alerts
|

Are the Effects of DES Over? A Tragic Lesson from the Past

Abstract: Diethylstilbestrol (DES), a transplacental endocrine-disrupting chemical, was prescribed to pregnant women for several decades. The number of women who took DES is hard to know precisely, but it has been estimated that over 10 million people have been exposed around the world. DES was classified in the year 2000 as carcinogenic to humans. The deleterious effects induced by DES are very extensive, such as abnormalities or cancers of the genital tract and breast, neurodevelopmental alterations, problems associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 101 publications
0
13
0
Order By: Relevance
“…We show for the first time that the estrogenic GPER1 activators, E2, BPA, and DES, cause numerical CA triggered by centriole overduplication, leading to karyotype instability in normal colon and CRC cell lines in a GPER1-dependent manner. Given that the sex hormone E2, the well-accepted endocrine-disrupting chemical BPA ( ECHA.eu , ( 30 )), and the known carcinogen DES ( 31 , 32 , 33 ) trigger the evolution of key CRC-prone lesions, our results may provide important clues for a possible role of estrogens in colon pathogenesis and shed light on the underlying mechanism that involves GPER1 function.…”
Section: Introductionmentioning
confidence: 85%
“…We show for the first time that the estrogenic GPER1 activators, E2, BPA, and DES, cause numerical CA triggered by centriole overduplication, leading to karyotype instability in normal colon and CRC cell lines in a GPER1-dependent manner. Given that the sex hormone E2, the well-accepted endocrine-disrupting chemical BPA ( ECHA.eu , ( 30 )), and the known carcinogen DES ( 31 , 32 , 33 ) trigger the evolution of key CRC-prone lesions, our results may provide important clues for a possible role of estrogens in colon pathogenesis and shed light on the underlying mechanism that involves GPER1 function.…”
Section: Introductionmentioning
confidence: 85%
“…Diethylstilbestrol (DES), a synthetic diphenol with powerful estrogenic properties, is considered the culprit of many somatic disorders in children and grandchildren of mothers treated during pregnancy ( 1 ). It has been estimated that worldwide, ~10 million people have been exposed to DES ( 2 ). However, very few studies investigated DES effects on neurodevelopment and psychiatric disorder occurrence, especially Autism Spectrum Disorders (ASD), in exposed children and their descendants.…”
Section: Introductionmentioning
confidence: 99%
“…Several patients exhibited various reproductive anomalies especially infertility, cysts in uterus, miscarriage. 12 Our previous study demonstrated the successful development of endometriosis by diethylstilbestrol (DES) instead of the traditional surgical induction in the animal model. 13 Further in this study we aimed to prove endometriosis induction of diethylstilbestrol in animal model ensues via immuneinflammatory pathway.…”
Section: Introductionmentioning
confidence: 99%